Group B Streptococcus and Pregnancy: Critical Concepts and Management Nuances. Issue 12 (December 2022) - Dotters-Katz, Sarah K.; Kuller, Jeffrey; Heine, R. Phillips; Wheeler, Sarahn M.
Abstract : Importance: Group B Streptococcus (GBS) is a common pathogen with an effective treatment. However, it remains a significant cause of neonatal sepsis, morbidity, and mortality. The screening and management of this infection are some of the first concepts learned during medical training in obstetrics. However, effective screening and evidence-based management of GBS are nuanced with many critical caveats. Objective: The objectives of this review are to discuss the essential aspects of GBS screening and management and to highlight recent changes to recommendations and guidelines. Evidence Acquisition: Original research articles, review articles, and guidelines on GBS were reviewed. Results: The following recommendations are based on review of the evidence and professional society guidelines. Screening for GBS should occur between 36 weeks and the end of the 37th week. The culture swab should go 2 cm into the vagina and 1 cm into the anus. Patients can perform their own swabs as well. Penicillin allergy testing has been shown to be safe in pregnancy. Patients with GBS in the urine should be treated at term with antibiotic prophylaxis, independent of the colony count of the culture. Patients who are GBS-positive with preterm and prelabor rupture of membranes after 34 weeks are not candidates for expectant management, as this population has higher rates of neonatal infectious complications. Patients with a history of GBS colonization in prior pregnancy who are GBS-unknown in this current pregnancy and present with labor should receive intrapartum prophylaxis. Work on the GBS vaccine continues. Conclusions: Although all of the efforts and focus on neonatal early-onset GBS infection have led to lower rates of disease, GBS still remains a major cause of neonatal morbidity and mortality requiring continued vigilance from obstetric providers. Target Audience: Obstetricians and gynecologists, family physicians. Learning Objectives: After participating in this activity, the provider should be better able to explain updates to GBS screening recommendations; identify indications for the GBS prophylaxis in common antepartum and intrapartum scenarios; and describe the correct method for performing the GBS swab.